The Utilization of Dioscorea Tuber in Self-Rising Starch: a Review - Mimi Harni; Tuty Anggraini; Rini Rini; Irfan Suliansyah (Journal of Applied Agricultural Science and Technology, 2022)
Self-rising starch is a development product of self-rising flour. This product  minimizes the process, especially in the salt and leavening agent weighing stage, so that it reduces the time in the serving process.  Self-rising flour is generally made of wheat flour.  Currently, due to some medical considerations, many people cannot consume this product. Based on some research results, gluten compound in wheat flour or wheat triggers for the development of type-1 diabetes. This fact has caused Indonesia to be ranked fifth in the world for the diabetic diseases. Thus, one of the ways to overcome this problem is by utilizing the raw materials originating from Indonesia too, namely tubers. Indonesia has a variety of tubers. Some of these tubers, however, have not been explored. These tubers have not only the function as the good sources of carbohydrates but also the bioactive compounds and more functional values, such as water soluble polysaccharides (WSP), diosgenin, inulin and glycemic index. They increase the functional properties of the starch that are produced. The tubers that currently have not been cultivated are the genus Dioscorea. The various tubers that are included in dioscorea family are uwi, gembili, gadung, tomberoso and jebubuk. All of these tubers are good sources of carbohydrates. Uwi, gembili and gadung are tubers that have been cultivated by the people for many years. On the hand, tomberoso and jebubuk tubers grow wildly in the forest that only become the foods for the wild animals in it. The starch derived from the disccorea tubers can be used as self-rising starch because it has the property as food developer. It contains high carbohydrates and bio-active compound, therefore, it is healthier to consume.